Identification of main fungal disease from hydroponic melon in greenhouse - Sumarni, E; Soesanto, L; Herliana, Okti; Leana, N W A; Priswanto, Priswanto; Purnomo, W H; Zulkifli, L (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Hydroponic melon is a method of cultivating melons and grown in a greenhouse. The melon cultivation has problems, namely plant diseases, even in a closed greenhouse. The melon plant disease caused huge losses in melon cultivation until the melon plants died. The purpose of this descriptive study was to identify the cause of the melon plant disease. Samples of sick melon plants were taken and grown on PDA media in the laboratory. The fungus that grows is identified based on the literature. The identification results showed that the main disease causing hydroponic melon plants in the greenhouse was the fungus Fusarium oxysporum f.sp. melonis. The fungi have crescent-shaped macroconidia with 1-3 septa, hyaline, thick walls, and form chlamydospores that are spherical in intercalary and hyaline.